Development of simple user-friendly commercial digital holographic microscope - Chee, Oi Choo (2011)
We report the development of a simple commercial digital holographic microscope. The hologram is recorded using a CCD sensor and numerically reconstructed to provide quantitative analysis of the object. The laser source is coupled via fibre optics and the opto-mechanical setup is flexible and customizable for either the reflection or transmission mode. The user-friendly software allows live reconstruction, simultaneously providing both the amplitude and phase images. System performance is improved with phase unwrapping and interferometric comparison. Additional features include various image enhancements, cross-sectional and line profiling, measurement and data analysis tools for quantitative 3D imaging and surface topography measurement. The performance of the product is tested on different micro devices, glass and silicon surfaces.